Village Autonomy and Land Disputes: Land Governance Politics in Traditional Villages in Papua, Indonesia, in the Issue of “All Eyes on Papua” - Sanjaya, Steven Tjahjadi; Alfikri, Muhammad Sultan; Khoiriyah, Khairunnisa; Fatkhuri, Fatkhuri (Jurnal Pemerintahan dan Kebijakan (JPK), 2025)
The agrarian conflict in Papua involving the Awyu indigenous community shows the challenges of the weak implementation of the principle of recognition within the framework of village autonomy and regulation. Although customary villages hold a position as a government unit recognized by the 1945 Constitution, in practice, they are not involved or included in the land licensing process on a large scale. This article analyzes this lack of involvement through the findings of literature studies and news sources that highlight the absence of an active role for village governments in this conflict. The findings show that there is a lack of coordination between the government, indigenous communities, and the private sector in land issues, which has an impact on the marginalization of civil society voices represented by indigenous communities. Therefore, it is necessary to strengthen village governance based on the principles of participation and justice to prevent the neglect of communal rights.